O uso de instrumentos financeiros e o nível de evidenciação qualitativa e quantitativa nas demonstrações contábeis de empresas não financeiras, no contexto das IFRS - Shinzato, Julio Mituo (2011)
The convergence to the international accounting standards introduced in the Brazilian accounting practices the fair value methodology from which financial assets and financial liabilities will start to be measured taking into consideration its fair market value. However, the complexity to understand, interpret and apply IAS 39 rules, recognized by the IASB, may cause distortions in the recognition and fair value measurement process with effects in the transparency of financial instruments disclosure. This process is compounded by the development of financial markets and risk exposures arising from financial instruments, requiring a better disclosure of risks associated to those instruments, especially derivatives. The study aimed to examine whether the disclosure level practiced by listed companies included in the BOVESPA index are complying with the requirements emanated from the international accounting standards. For this purpose, the financial statements for the period ended as at December 31, 2010 were object of the analysis as those statements were the first one presented according to the mandatory IFRS standards. In order to achieve the proposed objectives of the research, four index categories were developed (qualitative, quantitative, hedge accounting and risk management) based on disclosure provisions established by IFRS 7. The results obtained in the study revealed that the disclosure level for qualitative, quantitative, market risk and sensitive analysis is in line with IFRS standards. Nevertheless, more complexity accounting issues introduced by the international standards and not previously included into the Brazilian accounting practices framework, such as hedge accounting, still presents an incipient level of disclosure. Analogously, the result of the study did not take notice of greater transparency in the disclosure process with respect to credit and liquidity risk exposures, in contrast to the noticed for the market risk exposures where a high level disclosure might be attributed to a requirement enforced by CVM through a normative act